Skin care for healthy babies at term: A systematic review of the evidence. (January 2018) - Cooke, Alison; Bedwell, Carol; Campbell, Malcolm; McGowan, Linda; Ersser, Steven J.; Lavender, Tina
Abstract: Objectives: to identify what skin practices are important for the protection of baby skin in healthy term babies (0–6 months) and generate evidence-based conclusions to inform health professionals and parents. Design: eleven databases were searched for all empirical quantitative and qualitative research published between 2000–2015 which explored baby skin care for bathing and cleansing, nappy care, hair and scalp care, management of dry skin or baby massage, for healthy term babies up to 6 months old. Papers not published in English were excluded. A total of 3062 papers were identified. Pairs of reviewers assessed all citations and extracted data independently. There were 26 included papers: 16 RCTs, 3 non-randomised experimental studies, 1 mixed-methods study and 6 qualitative studies. Primary and secondary outcome measures were analysed using meta-analysis or narrative descriptive statistics. Synthesis of qualitative data was not possible due to disparity of the evidence. Findings: from the small numbers of studies with comparable data, there was no evidence of any significant differences between tested wash products and water or tested baby wipes and water. There was some evidence to suggest that daily use of full-body emollient therapy may help to reduce the risk of atopic eczema in high risk babies with a genetic predisposition to eczema; however, the use of olive oil or sunflower oil for baby dry skin may adversely affect skin barrier function. There was no evidence about hair/scalp care or baby massage. Qualitative research indicates that parents and health professionals believe that water alone is best. Key conclusions: meta-analysis was restricted due to the lack of consistency of study outcome measures. Although there is considerable RCT evidence comparing the use of specific products against water alone, or another product, for bathing, cleansing and nappy care, the power of this evidence is reduced due to inconsistency of outcome measures in terms of outcome, treatment site or time-point. The development of a core outcome measure set is advocated for trials assessing skin care practices. Implications for practice: this review offers health professionals best evidence available on which to base their advice. Of those studies with comparative outcomes, the evidence indicates no difference between the specific products tested and water alone; offering parents a choice in their baby skin care regimen. Protocol available:http://www.crd.york.ac.uk/PROSPEROFILES/28054_PROTOCOL_20151009.pdf Highlights: Clear and current clinical guidelines for baby skin care are urgently needed. Adherence to reporting guidelines is poor and a core outcome set is required. Difficult to link skin care and eczema as few studies assess babies post-6 months. There is often little difference between the effect of skin product and water alone. Effect of baby massage on skin integrity requires further investigation.